Penambahan tepung buah mengkudu (morinda citrifolia l) pada pakan terhadap perubahan aktivitas fagositosis, total eritrosit dan hemoglobin ikan nila (oreochromis niloticus) - Irma Yunita; Henni Syawal; Iesje Lukistyowati (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
This research was conducted from Mei to September 2015 in the Laboratory of Parasitic Diseases of Fish Faculty of Fisheries and Marine Science, University of Riau. The purpose of this reseach was to knowing the addition of flour noni (Morinda citrifolia L) on feed to change the phagocytic activity, total of erythrocytes and hemoglobin of tilapia (Oreochromis niloticus) infected Streptococcus iniae. This research used five treatments, 1) Kn: negative control (without a solution of addition flour noni (Morinda citrifolia L) and without the infection of Streptococcus iniae.), 2) Kp: positive control (without giving a solution of addition of flour noni (Morinda citrifolia L) and the infection Streptococcus iniae) 3) P1: addition flour noni (Morinda citrifolia L) 3 g/kg feed) P2: addition flour noni (morinda citrifolia l) 6 g/kg feed) P3: addition flour noni (Morinda citrifolia L) 9 g/kg feed). The research shows that the addition of flour noni (Morinda citrifolia L) on feed do impact the condition of fish blood because visible from the phagocytic activity is ranged between 35,33-56,66%, total erythrocytes 1,23-2,20 x106 cell/mm3, and hemoglobin is ranged between 4,66-6,33 gr/%.